The works in logic by Bosniac authors in Arabic - Ljubović, Amir, 1945- (Islamic Philosophy, Theology and Science. Texts and Studies, 2008)
The book offers and explains the hypothesis that the end of the 13th century does not denote the "final stage" and the "stage of decay" of Arabic logic as the "Aristotelian logic" continues its life and development in the following period in Bosnia and Herzegovina ̶ either as a subject within the educational system, or as general propaedeutics for each scientific thought ̶ where it had skilled interpreters. The book proves that the people of Bosnia and Herzegovina used almost the same way to compose writings in the field of logic: one in Latin within West-European cultural and theological tradition, and the others in Arabic, within Arabic-islamic tradition.